PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS PERMAINAN UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PKn MATERI PENGARUH GLOBALISASI PADA SISWA KELAS IV SD 6 PUYOH - Ashfiyah Ashfiyah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractThis study aims to increase the motivation and achievement of students in grade I V SD 6 Puyoh in the second semester of the 2017/2018 academic year in Civics by applying the contextual teaching and learning (CTL) approach based on game methods.To achieve this goal, this study was designed in two cycles. The procedure in each cycle includes the stages: 1) planning, 2) implementation, 3) observation, 4) reflection.The effectiveness of actions in each cycle is measured from the results of observations described, interpreted, and then reflected to determine corrective actions in the next cycle.Research actions taken as much as two cycles of the results obtained in the first cycle, 20 students already are 14 students or 7 0 % achieve mastery that has been set while the remaining 4 students or 30 % not achieve mastery. The highest score obtained by students is 80 while the lowest score is 50, the average student learning outcome is 74 . The increase in the average learning outcomes in the first cycle was 13% of the average pre - cycle achievement . Cycle II data shows that of the 20 students there were 19 students or 95 % had reached the specified completeness while the remaining 1 child or 5 % had not reached completeness. The highest score obtained by students is 100 while the lowest score is 70. The average student learning outcomes are 80 , 3 . Improved learning outcomes that occur in cycle II amounted to 7.5 %Depending on the action concluded the implementation of cooperative learning model to approach Contextual Teaching and Learning (CTL) based game method , can improve student motivation and achievement of grade I V SD 6 Puyoh the second semester of 2017/2018 school year on the subjects of civics materials globalization. D ith the increasing student motivation to result in increased student achievement.Keyword : CTL, Motivation, achievement, Civics